PALEOGEOGRAPHIC EVOLUTION OF THE ATHENS BASIN FROM UPPER MIOCENE TO PRESENT - Παπανικολάου Δ.; Μπάση Ε. Κ.; Κράνης Χ.; Δανάμος Γ. (Bulletin of the Geological Society of Greece, 2018)
The Athens basin represents a complex neotectonic asymmetric graben bounded by NNE-SSW marginal faults with much higher activity along the western side in Egaleo and Parnitha Mts than along the eastern side along Pendeli and Hymettos Mts. The activity started during Late Miocene as the presence of sedimentary sequences indicates, continental and lacustrine in the west and north and coastal marine in the southeast. An E-W fault zone divided the basin in a northern subsided part - where lakes were dominating throughout Late Miocene - Pliocene - and a southern part where lakes were occurring only during Late Miocene in the central - western part, whereas shallow marine environments dominated in the south and southeast during Late Miocene – Pliocene with the coastline being very close to the present day Acropolis and Philopapou hills. The central eastern area was in a high position with the Alpine bedrocks under erosion and constituted a barrier towards the south. This situation changed before the middle Pleistocene when Kifissos River was formed cutting through the hilly area and connected the northern drainage system with the south, which resulted in the saturation of the remnant lakes of the northern segment. At the same period very thick fans were formed at the foothills of the surrounding mountains, covering the previous neogene sediments and/or Alpine rocks. Ever since the paleogeography was similar to the present geography during the inter-glacial periods and substantially different with the coastline along the present isobath of-120m during the glacial periods, like the Wurm.